2007
DOI: 10.1007/s10834-007-9071-x
|View full text |Cite
|
Sign up to set email alerts
|

Rhetoric and Reality of Economic Self-sufficiency Among Rural, Low-Income Mothers: A Longitudinal Study

Abstract: This study examined the contributions of maternal labor force participation and marital status on economic self-sufficiency over time for rural mothers. Data were from 174 rural families participating in three waves of data collection in Rural Families Speak. χ 2 and multiple logistic regression were utilized. Results revealed only one-third of mothers moved toward economic self-sufficiency over three years. Maternal education, employment status, and weekly work hours were associated with improved economic wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Simmons et al . () and Banerjee () found that women with fewer children were more likely to achieve economic solvency than those with more children. Several articles mentioned the fact that women may choose or be forced to be economically insolvent to provide adequate mothering (Rosman & Yoshikawa , Chantler , Lundstrom & Twine ).…”
Section: Resultsmentioning
confidence: 99%
“…Simmons et al . () and Banerjee () found that women with fewer children were more likely to achieve economic solvency than those with more children. Several articles mentioned the fact that women may choose or be forced to be economically insolvent to provide adequate mothering (Rosman & Yoshikawa , Chantler , Lundstrom & Twine ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons should be made with similar samples of urban residents because these results may provide additional support for considering rurality as a unique context of human development (Simmons et al, 2007b). Kohler et al (2004) suggest that social workers be schooled in integrating informal family support into service delivery plans.…”
Section: Summary and Public Policy Recommendationsmentioning
confidence: 96%
“…Human capital, in the form of education, increases women's employment prospects, earnings, health and social and occupational status (Blau 1998;Mirowsky and Ross 2003;Simmons et al 2007a;Simmons et al 2007b;Thompson 1993;Wirt et al 1998). Between 1970 and 2000, annual median incomes were substantially higher for women with a bachelor's degree compared to those with only a high school degree (Freeman 2004).…”
Section: Promoting Educationmentioning
confidence: 99%
“…Previous studies have found a significant relationship between mothers' demographic (e.g., age, race, number of children) and employment related characteristics (e.g., hours and weeks of work) and outcome variables-their income and marital status (Dixon and Rettig 1994;Mauldin 1990;Mauldin and Mimura, 2007;Simmons et al 2007b;Smock 1993Smock , 1994Zhan and Pandey 2004a, b). These factors must be accounted for when examining the effect of education on income and marital status.…”
Section: Other Demographic and Employment Factorsmentioning
confidence: 99%